2019
DOI: 10.1089/scd.2019.0045
|View full text |Cite
|
Sign up to set email alerts
|

mRNA Reprogramming of T8993G Leigh's Syndrome Fibroblast Cells to Create Induced Pluripotent Stem Cell Models for Mitochondrial Disorders

Abstract: Early molecular and developmental events impacting many incurable mitochondrial disorders are not fully understood and require generation of relevant patient-and disease-specific stem cell models. In this study, we focus on the ability of a nonviral and integration-free reprogramming method for deriving clinical-grade induced pluripotent stem cells (iPSCs) specific to Leigh's syndrome (LS), a fatal neurodegenerative mitochondrial disorder of infants. The cause of fatality could be due to the presence of high a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 62 publications
1
19
0
Order By: Relevance
“…With iPSCs, some of these problems can be resolved as fibroblast derived from diseased patients could be reprogrammed and potentially differentiated into any cell/tissue to better elucidate the pathological mechanism of a specific mitochondrial disorder on various cells/tissues. Many recent studies have demonstrated the potential for generating human iPSC patient-specific models from LS carrying mutations in MT-ATP6 and MT-ND5 genes ( Galera-Monge et al, 2016 ; Zurita-Diaz et al, 2016 ; Grace et al, 2019 ). Another study combined somatic cell nuclear transfer (SCNT) and iPSC technology to perform a metabolic rescue in the iPSCs generated from these patients, demonstrating the significant possibilities that iPSC models hold, as they could potentially be used to simultaneously study pathogenesis and develop treatments for patients with LS and other mitochondrial diseases ( Ma et al, 2015 ).…”
Section: Disease Models For Lsmentioning
confidence: 99%
“…With iPSCs, some of these problems can be resolved as fibroblast derived from diseased patients could be reprogrammed and potentially differentiated into any cell/tissue to better elucidate the pathological mechanism of a specific mitochondrial disorder on various cells/tissues. Many recent studies have demonstrated the potential for generating human iPSC patient-specific models from LS carrying mutations in MT-ATP6 and MT-ND5 genes ( Galera-Monge et al, 2016 ; Zurita-Diaz et al, 2016 ; Grace et al, 2019 ). Another study combined somatic cell nuclear transfer (SCNT) and iPSC technology to perform a metabolic rescue in the iPSCs generated from these patients, demonstrating the significant possibilities that iPSC models hold, as they could potentially be used to simultaneously study pathogenesis and develop treatments for patients with LS and other mitochondrial diseases ( Ma et al, 2015 ).…”
Section: Disease Models For Lsmentioning
confidence: 99%
“…show obvious deficits in cell growth (Grace et al, 2019). Given the fact the neuroectoderm 244 expansion phase happens during days 7-10, the degeneration of the MT-ATP6/PDH organoids 245 after embedding may recapitulate these previously reported observations.…”
Section: Leigh Syndrome Associated Mutations Disrupt Corticogenesis Imentioning
confidence: 52%
“…Defective organoid formation in this cell line was significantly higher than control and the other two LS cell lines (Figure S4B). A previous report showed that when iPSCs generated from fibroblasts harboring the same T8993G mitochondrial mutation were differentiated into EBs, there was rapid regression and death after 7 days in suspension, while the monolayer culture did not show obvious deficits in cell growth (Grace et al, 2019). Given the fact the neuroectoderm expansion phase happens during days 7-10, the degeneration of the MT-ATP6/PDH organoids after embedding may recapitulate these previously reported observations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Heteroplasmy often appears to remain stable following directed differentiation [ 45 , 87 , 91 ]. Therefore, it is practical to check heteroplasmy levels before and after differentiation to ensure they are within the phenotypic range for patients with the same mutation [ 45 , 171 , 172 ]. Additionally, use of mitochondrial targeted editing strategies like mitoTALENs and DdCBEs could help achieve a greater level of control prior to differentiation [ 80 , 81 , 83 ].…”
Section: Discussionmentioning
confidence: 99%